A composition design method for 6XXX series high-strength aluminum alloy welding filler material

By determining the ideal weld composition in aluminum alloy welding and calculating the composition of the newly welded filler material, the small isometric grain structure is formed, the problem of insufficient strength of the existing aluminum alloy wire is solved, and the high strength and high ductility of the welded joints are achieved, meeting the welding manufacturing needs of high-end equipment.

CN117817116BActive Publication Date: 2025-03-18SUZHOU UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311873129.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-03-18
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

The existing aluminum alloy welding wire has a single variety, and the strength of the welded joint can only reach 60% to 70% of the strength of the base material, making it difficult to meet the welding manufacturing needs of high-end equipment.

Method used

By determining the composition of the welding base material, setting the ideal weld composition, and calculating the composition of the newly welded filler material, including Si, Mg, Cu, Zn and refining agent, forming a fine isoxial grain structure, improving the mechanical properties of the weld and heat-affected zone.

Benefits of technology

Effectively refine weld grains, improve the strength and ductility of welds, improve the strength of weld joints, and meet the welding manufacturing needs of high-end equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117817116B_ABST
    Figure CN117817116B_ABST
Patent Text Reader

Abstract

The present invention discloses a composition design method of a 6XXX series high-strength aluminum alloy welding filling material, comprising the following steps: determining the composition of the welding parent material; setting an ideal weld composition according to the parent material composition, the weld should have a fine and uniform equiaxed grain structure and the ability to quickly precipitate a strengthening phase through post-weld baking, ensuring that the weld and the heat-affected zone have excellent mechanical properties; using a filler material and a parent material of known composition for welding, and after determining the welding process, measuring the fusion ratio and the volatility of easily burnt elements; according to the parent material composition, the ideal weld composition, the fusion ratio and the volatility of easily burnt elements, the composition of the new welding filling material is calculated by the following formula: New welding filling material composition = ideal weld composition / (1-fusion ratio)*(1-volatility)-parent material composition*fusion ratio / (1-fusion ratio). The welding filling material designed by this method can improve the strength of the welded joint and meet the welding manufacturing requirements of high-end equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material welding, and in particular to a composition design method for a 6XXX series high-strength aluminum alloy welding filler material. Background Art

[0002] Aluminum alloys have the advantages of low density, high specific strength, good corrosion resistance, and easy plastic forming. They have been widely used in railways, road transportation systems, ships, military equipment and other fields. However, aluminum alloys also have the characteristics of high thermal conductivity, fast solidification rate, high thermal expansion coefficient, and wide solidification temperature range. During welding, defects such as pores, thermal cracks and softening usually appear at the weld joints, which deteriorate the mechanical properties of the overall component. Porosity is the main source of cracks in the fusion zone of the weld and has a substantial impact on fatigue life. The softening problem of the weld and the softening problem of the heat-affected zone cause the weld joint to become the weak zone of the entire component, which limits the industrial application of aluminum alloys. Therefore, obtaining aluminum alloy welded joints with less pores, no thermal cracks and high strength is a goal that many researchers have been committed to achieving.

[0003] For a given welding base material, the composition of aluminum alloy welding wire has a very important influence on the microstructure and mechanical properties of the welded joint. In engineering manufacturing, welded joints are generally not subject to further processing and deformation, and in most cases cannot be further heat-treated and strengthened. Therefore, in most cases, the performance of welded joints can only be regulated by optimizing the composition of welding wire and welding process.

[0004] At present, the commonly used aluminum alloy welding wires in industry are divided into four categories according to the alloy grades, namely 1XXX series, 2XXX series (ER2319), 4XXX series (ER4043, ER4047) and 5XXX series (ER5554, ER5654, ER5356 and ER5183). Compared with the number of aluminum alloys, the varieties of aluminum alloy welding wires are single. 2XXX series welding wires can only weld 2XXX series aluminum alloys, 4XXX series welding wires can generally only be used to weld 6XXX series alloys, and 5XXX series welding wires are almost used to weld all types of aluminum alloy parent materials, which is obviously unreasonable. Moreover, the strength of the welded joint can only reach 60% to 70% of the strength of the parent material. Therefore, many patents are based on these commonly used welding wires and improve the performance of welded joints by microalloying. Patent CN 114193021 A adds Sr spheroidized needle-shaped eutectic silicon to ER4043 and adds Ti and B to generate TiB 2 and Al 3Ti refines grains. Patent CN 110227892 A adds rare earth elements Nd and Ce to 5XXX aluminum alloy welding wire to reduce weld porosity and improve weld strength and corrosion resistance. Patent CN 116000498A proposes an Al-Mg-Mn-Zn-Zr welding wire based on ER5356. However, these welding wires contribute little to the improvement of weld joint strength and cannot meet the welding manufacturing requirements of high-end equipment. Summary of the invention

[0005] The purpose of the present invention is to propose a composition design method for 6XXX series high-strength aluminum alloy welding filler materials, which can improve the strength of welded joints and meet the welding manufacturing requirements of high-end equipment.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] A composition design method for a 6XXX series high-strength aluminum alloy welding filler material, characterized in that it comprises the following steps:

[0008] Step 1: Determine the composition of the welding base material;

[0009] Step 2: According to the composition of the parent material, set the ideal weld composition. The ideal weld composition should make the weld have a fine and uniform equiaxed grain structure and have the ability to quickly precipitate the strengthening phase after baking after welding, so as to ensure that the weld and heat-affected zone have excellent mechanical properties;

[0010] Step 3: Use filler materials and base materials with known compositions for welding. After determining the welding process, measure the fusion ratio and the volatilization rate of the easily burnt elements.

[0011] Step 4: Based on the base metal composition, ideal weld composition, fusion ratio and volatilization rate of easily burned elements, the composition of the new welding filler material is calculated by the following formula:

[0012] The composition of the new welding filler material = ideal weld composition / (1-fusion ratio)*(1-volatilization rate)-base material composition*fusion ratio / (1-fusion ratio).

[0013] Furthermore, the composition of the welding base material in step 1 is at least one of the following three types:

[0014] Base material 1: Mg 0.8-0.9wt%, Si 0.9~1.0wt%, Cu 0.3-0.4wt%, Mn 0.6-0.65wt%, Cr 0.2-0.25wt%, Ti 0.025-0.03wt%, Fe ≤ 0.15wt%, Zn < 0.05wt%, Al as the balance;

[0015] Base material 2: Mg0.82-0.9wt%, Si0.95~1.1wt%, Cu0.4-0.5wt%, Mn0.55-0.65wt%, Cr0.2-0.3wt%, Ti0.025-0.03wt%, Fe≤0.15wt%, Zn<0.05wt%, Al is the balance;

[0016] Base material 3: Mg 0.9-1.0wt%, Si 1.1~1.2wt%, Cu 0.55-0.65wt%, Mn 0.6-0.7wt%, Cr 0.2-0.25wt%, Ti 0.025-0.03wt%, Fe≤0.15wt%, Zn<0.05wt%, and Al as the balance.

[0017] Furthermore, the post-weld baking in step 2 includes pre-aging before welding and two-stage baking treatment after welding.

[0018] Furthermore, the filler material of known composition in step 3 is 2XXX series, 4XXX series or 5XXX series aluminum alloy.

[0019] Furthermore, the welding process in step 3 is one or more of laser welding, electron beam welding, cold metal transfer welding, non-melting inert gas shielded arc welding, melting inert gas shielded welding and stir friction welding.

[0020] Furthermore, the filler material with known composition and the new welding filler material in steps 3 and 4 are in the form of one or more of the following three types: powder of 10-200 um, flakes of 50-1000 um, and welding wire of 0.5-3.2 mm diameter.

[0021] Furthermore, the pre-aging method before welding is: 140-220°C, 1-3h; the two-stage baking treatment method after welding is: baking temperature is 180-200°C, time is 0.5h, after air cooling to room temperature, a second baking is performed, the baking temperature is 180-200°C, time is 0.5h, and then air cooling to room temperature.

[0022] Furthermore, the fusion ratio in step 3 is calculated as follows: fusion ratio = cross-sectional area of ​​melted parent metal / (cross-sectional area of ​​melted parent metal + cross-sectional area of ​​filler metal in weld).

[0023] Furthermore, the volatility of the easily burnt elements in step 3 is calculated as follows: volatility = (Mg or Zn content calculated based on the fusion ratio - Mg or Zn content of the actual weld) / Mg or Zn content of the actual weld, and the easily burnt elements are Mg and Zn.

[0024] Furthermore, the composition of the new welding filler material in step 4 is: Si = 4.5 ~ 22.65wt.%, Mg = 0.9 ~ 1.40wt.%, Cu = 1.9 ~ 4.19wt.%, Zn = 0.9 ~ 2.39wt.%, refiner = 0.1 ~ 0.24wt.%, Al is the balance, wherein the composition of the refiner is: Ti = 2wt.%, C = 0.3wt.%, B = 0.2wt.%, Al is the balance.

[0025] The beneficial effects of the present invention are:

[0026] 1. The composition of welding filler materials is derived from the composition of the base material and the weld, which effectively shortens the time required for welding filler material design and reduces a lot of experimental verification work.

[0027] 2. Welding using the welding filler material provided by the present invention can effectively refine the weld grains, form fine equiaxed crystals, reduce the thermal cracking tendency of the weld, and improve the strength and ductility of the weld.

[0028] 3. Pre-aging and post-welding baking treatment of the base material can improve the strength of the heat-affected zone. At the same time, post-welding baking treatment can quickly precipitate β", θ' and Q' composite strengthening phases in the weld, thereby simultaneously improving the strength of the weld and the heat-affected zone.

[0029] 4. It can improve the strength of welded joints and meet the welding manufacturing requirements of high-end equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a flow chart of a composition design method for a 6XXX series high-strength aluminum alloy welding filler material of the present invention;

[0031] Figure 2 The cross-sectional morphology of the weld seam of the welded joint obtained in Test Example 1;

[0032] Figure 3 Comparison of microstructure photos of the weld center of the weld joint without filler material and with 0.7 mm thin sheet added in Test Example 1;

[0033] Figure 4 This is a comparison diagram of the microhardness distribution of three laser welded joints in Experimental Example 1;

[0034] Figure 5 This is a microstructure photograph of the weld center of the weld joint obtained in Test Example 2;

[0035] Figure 6 This is a comparison diagram of the microhardness distribution of the welded joint in Test Example 2. DETAILED DESCRIPTION

[0036] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0037] Embodiment: A composition design method for a 6XXX series high-strength aluminum alloy welding filler material comprises the following steps:

[0038] Step 1: Determine the composition of the welding base material;

[0039] Step 2: According to the composition of the parent material, set the ideal weld composition. The ideal weld composition should make the weld have a fine and uniform equiaxed grain structure and have the ability to quickly precipitate the strengthening phase after baking after welding, so as to ensure that the weld and heat-affected zone have excellent mechanical properties;

[0040] Step 3: Use filler materials and base materials with known compositions for welding. After determining the welding process, measure the fusion ratio and the volatilization rate of the easily burnt elements.

[0041] Step 4: Based on the base metal composition, ideal weld composition, fusion ratio and volatilization rate of easily burned elements, the composition of the new welding filler material is calculated by the following formula:

[0042] The composition of the new welding filler material = ideal weld composition / (1-fusion ratio)*(1-volatilization rate)-base material composition*fusion ratio / (1-fusion ratio).

[0043] The composition of the welding base material in step 1 is at least one of the following three types:

[0044] Base material 1: Mg 0.8-0.9wt%, Si 0.9~1.0wt%, Cu 0.3-0.4wt%, Mn 0.6-0.65wt%, Cr 0.2-0.25wt%, Ti 0.025-0.03wt%, Fe ≤ 0.15wt%, Zn < 0.05wt%, Al as the balance;

[0045] Base material 2: Mg0.82-0.9wt%, Si0.95~1.1wt%, Cu0.4-0.5wt%, Mn0.55-0.65wt%, Cr0.2-0.3wt%, Ti0.025-0.03wt%, Fe≤0.15wt%, Zn<0.05wt%, Al is the balance;

[0046] Base material 3: Mg 0.9-1.0wt%, Si 1.1~1.2wt%, Cu 0.55-0.65wt%, Mn 0.6-0.7wt%, Cr 0.2-0.25wt%, Ti 0.025-0.03wt%, Fe≤0.15wt%, Zn<0.05wt%, and Al as the balance.

[0047] The post-weld baking in step 2 includes pre-aging before welding and two-stage baking after welding.

[0048] The filler material of known composition in step 3 is 2XXX series, 4XXX series or 5XXX series aluminum alloy.

[0049] The welding process in step 3 is one or more of laser welding, electron beam welding, cold metal transfer welding, non-melting inert gas shielded arc welding, melting inert gas shielded welding and stir friction welding.

[0050] The filler material with known composition and the new welding filler material in steps 3 and 4 are in the form of one or more of 10-200 um powder, 50-400 um flakes and 0.5-3.2 mm diameter welding wire.

[0051] The pre-aging method before welding is: 140-220° C., 1-3 h; the double-stage baking treatment method after welding is: 180-200° C., 0.5 h air cooling + 0.5 h air cooling.

[0052] The calculation method of the fusion ratio in step 3 is: fusion ratio = cross-sectional area of ​​melted parent metal / (cross-sectional area of ​​melted parent metal + cross-sectional area of ​​filler metal in weld).

[0053] The volatility of the easily burnt elements in step 3 is calculated as follows: volatility = (Mg or Zn content calculated based on the fusion ratio - Mg or Zn content of the actual weld) / Mg or Zn content of the actual weld, and the easily burnt elements are Mg and Zn.

[0054] The composition of the new welding filler material in step 4 is: Si = 4.5 ~ 22.65wt.%, Mg = 0.9 ~ 1.40wt.%, Cu = 1.9 ~ 4.19wt.%, Zn = 0.9 ~ 2.39wt.%, refiner = 0.1 ~ 0.24wt.%, Al is the balance, wherein the composition of the refiner is: Ti = 2wt.%, C = 0.3wt.%, B = 0.2wt.%, Al is the balance.

[0055] Test Example 1

[0056] The base material composition selected in this test example 1 is:

[0057] Si Mg Cu Cr Mn Ti Fe Zn Al 0.98wt.% 0.82wt.% 0.44wt.% 0.24wt.% 0.61wt.% 0.03wt.% 0.11wt.% 0.01wt.% margin

[0058] The ideal weld composition is set as follows: Si = 10wt.%, Mg = 1wt.%, Cu = 2wt.%, Zn = 1wt.%, refiner = 0.1wt.%, and Al as the balance. Among them, the composition of the refiner is: Ti = 2wt.%, C = 0.3wt.%, B = 0.2wt.%, and Al as the balance.

[0059] CMT+Synchropulse welding was performed using 1.2mm diameter 4XXX series welding wire ER4043. Two base materials 2 with dimensions of 100mm×40mm×2.3mm were butt welded. The welding parameters were: wire feeding speed of 3.5m / min, welding speed of 10mm / s. The cross-sectional morphology of the weld was obtained, as shown in the figure. Figure 2 shown.

[0060] According to the formula: fusion ratio = cross-sectional area of ​​molten parent metal / (cross-sectional area of ​​molten parent metal + cross-sectional area of ​​filler metal in weld), the fusion ratio is 58.37%. At the same time, the chemical composition of the weld is measured as follows:

[0061] Si Mg Cu Cr Mn Ti Fe Zn Al 2.67wt.% 0.47wt.% 0.30wt.% 0.19wt.% 0.35wt.% 0.04wt.% 0.17wt.% 0.11wt.% margin

[0062] The composition of 4XXX series welding wire ER4043 is:

[0063] Si Mg Cu Cr Mn Ti Fe Zn Al 4.9wt.% 0.05wt.% 0.30wt.% - 0.05wt.% 0.20wt.% 0.8wt.% 0.1wt.% margin

[0064] The composition of the weld is obtained according to the fusion ratio:

[0065] Si Mg Cu Cr Mn Ti Fe Zn Al 2.61wt.% 0.50wt.% 0.38wt.% 0.14wt.% 0.38wt.% 0.10wt.% 0.40wt.% 0.05wt.% margin

[0066] The composition of the measured weld is close to that calculated from the fusion ratio. For the easily burned element Mg, according to the formula: (Mg content calculated from the fusion ratio - Mg content in the actual weld) / Mg content in the actual weld, its volatility can be calculated to be 6%.

[0067] According to the following formula:

[0068] New welding filler material composition = ideal weld composition / (1-fusion ratio) * (1-volatilization rate) - parent material composition * fusion ratio / (1-fusion ratio)

[0069] The composition of the new welding filler material is:

[0070] Si = 22.65wt.%, Mg = 1.40wt.%, Cu = 4.19wt.%, Zn = 2.39wt.%, refiner = 0.24wt.%, Al as the balance. The composition of the refiner is: Ti = 2wt.%, C = 0.3wt.%, B = 0.2wt.%, Al as the balance.

[0071] The new welding filler material obtained by melting was cut into thin sheets of 0.2mm and 0.7mm thickness by wire cutting, and placed at the base material joint with the size of 120mm×40mm×2.3mm for laser welding. The base material has been pre-aged at 140℃ for 1 hour before welding. The process parameters of laser welding are: laser power 2400W, welding speed 50mm / s, laser beam circular swing, swing amplitude 1.2mm, swing frequency 100Hz. After welding, the welded plate was baked at 180℃ for 0.5 hours and cooled to room temperature, and then the welded plate was placed at 180℃ for 0.5 hours and cooled to room temperature. Figure 3 The microstructure of the weld center of the weld joint without filler material and with 0.7 mm thin sheet added. The mass fraction of the chemical composition of the weld with 0.7 mm thin sheet added is:

[0072] Si Mg Cu Cr Mn Ti Fe Zn Al 7.71wt.% 0.90wt.% 1.89wt.% 0.27wt.% 0.40wt.% 0.04wt.% 0.06wt.% 0.71wt.% margin

[0073] Compared with the laser welded joint without filler material, the content of white precipitate phase in the weld increased significantly after adding 0.7mm flake filler material. Moreover, the grain structure of the weld with filler material is finer. Figure 4 The following are the microhardness distribution diagrams of three laser welded joints. For welded joints without welding filler materials, the average hardness of the weld is 65.77HV. After adding 0.2mm thin sheets, the average hardness of the weld increases to 76.16HV. When 0.7mm thin sheets are added, the average hardness of the weld increases to 113.8HV. Moreover, after pre-aging before welding and baking after welding, the average hardness of the heat-affected zone of the welded plates with 0.2mm and 0.7mm thin sheets increases by 36.57% compared with the welded plates without baking treatment (no filler materials).

[0074] Test Example 2

[0075] The base material composition selected in this test example 2 is:

[0076] Si Mg Cu Cr Mn Ti Fe Zn Al 0.98wt.% 0.82wt.% 0.44wt.% 0.24wt.% 0.61wt.% 0.03wt.% 0.11wt.% 0.01wt.% margin

[0077] A new welding filler material with a diameter of 1.2 mm was used, and the composition was: Si = 10wt.%, Mg = 1wt.%, Cu = 2wt.%, Zn = 1wt.% welding wire, refiner (Ti = 2wt.%, C = 0.3wt.%, B = 0.2wt.%, Al as the balance) = 0.1wt.% for CMT+Synchropulse welding. Two base materials with a size of 100mm×40mm×2.3mm were pre-aged at 140°C for 1 hour before butt welding. The wire feeding speed was 3.7m / min and the welding speed was 9mm / s. After welding, the weld plate was baked at 180°C for 0.5 hours and then cooled to room temperature. The weld plate was baked at 180°C for 0.5 hours and then cooled to room temperature. Figure 5 It is the microstructure of the weld center of the weld joint. The mass fraction of the chemical composition of the weld is:

[0078] Si Mg Cu Cr Mn Ti Fe Zn Al 4.87wt.% 0.57wt.% 1.19wt.% 0.14wt.% 0.27wt.% 0.10wt.% 0.13wt.% 0.08wt.% margin

[0079] The new welding filler material increases the content of Si, Cu, Ti and other elements in the weld. On the one hand, the increase of Ti element refines the grain structure in the center of the weld. On the other hand, during the solidification of the molten pool, solute elements such as Mg, Si, Cu, Fe, and Mn tend to segregate at the grain boundaries to form white precipitation phases. Figure 6 The following is a comparison of the microhardness distribution of the welded joint. Compared with the microhardness of the T6 state base material 2 welded joint using ER4043 welding wire, the average hardness of the weld after adding the new welding filler material increased from 71.23HV to 83.94HV. In addition, after pre-aging before welding and baking after welding, the average hardness of the heat affected zone also increased.

[0080] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A composition design method for 6XXX series high-strength aluminum alloy welding filler material, characterized in that: The following steps are involved: Step 1: Determine the composition of the welding base material; Step 2: According to the composition of the parent material, set the ideal weld composition. The ideal weld composition should make the weld have a fine and uniform equiaxed grain structure, and have the ability to quickly precipitate the strengthening phase after baking after welding, so as to ensure that the weld and heat-affected zone have excellent mechanical properties; Step 3: Use filler materials and base materials with known compositions for welding. After determining the welding process, measure the fusion ratio and the volatilization rate of the easily burnt elements. Step 4: Based on the base metal composition, ideal weld composition, fusion ratio and volatilization rate of easily burned elements, the composition of the new welding filler material is calculated by the following formula: Composition of new welding filler material = ideal weld composition / (1-fusion ratio)*(1-volatilization rate)-base material composition*fusion ratio / (1-fusion ratio); The composition of the welding base material in step 1 is at least one of the following three types: Base material 1: Mg0.8-0.9wt%, Si0.9~1.0wt%, Cu0.3-0.4wt%, Mn0.6-0.65wt%, Cr0.2-0.25wt%, Ti0.025-0.03wt%, Fe≤0.15wt%, Zn<0.05wt%, Al is the balance; Base material 2: Mg0.82-0.9wt%, Si0.95~1.1wt%, Cu0.4-0.5wt%, Mn0.55-0.65wt%, Cr0.2-0.3wt%, Ti0.025-0.03wt%, Fe≤0.15wt%, Zn<0.05wt%, Al as the balance; Base material 3: Mg0.9-1.0wt%, Si1.1~1.2wt%, Cu0.55-0.65wt%, Mn0.6-0.7wt%, Cr0.2-0.25wt%, Ti0.025-0.03wt%, Fe≤0.15wt%, Zn<0.05wt%, Al as the balance; The post-weld baking in step 2 includes pre-aging before welding and two-stage baking after welding; The filler material with known composition and the new welding filler material in steps 3 and 4 are in the form of one or more of 10-200 um powder, 50-1000 um flakes and 0.5-3.2 mm diameter welding wire; The pre-aging temperature before welding is 140-220°C, and the time is 1-3h; the two-stage baking treatment after welding is: the baking temperature is 180-200°C, the time is 0.5h, and after air cooling to room temperature, a second baking is performed, the baking temperature is 180-200°C, the time is 0.5h, and after baking, the air is cooled to room temperature; The composition of the new welding filler material described in step 4 is: Si=4.5~22.65 wt.%, Mg=0.9~1.40 wt.%, Cu=1.9~4.19 wt.%, Zn=0.9~2.39 wt.%, refiner=0.1~0.24 wt.%, and Al is the balance, wherein the composition of the refiner is: Ti=2 wt.%, C=0.3 wt.%, B=0.2 wt.%, and Al is the balance.

2. The composition design method of a 6XXX series high-strength aluminum alloy welding filler material according to claim 1, characterized in that: The filler material of known composition in step 3 is 2XXX series, 4XXX series or 5XXX series aluminum alloy.

3. The composition design method of a 6XXX series high-strength aluminum alloy welding filler material according to claim 1, characterized in that: The welding process in step 3 is one or more of laser welding, electron beam welding, cold metal transfer welding, non-melting inert gas shielded arc welding, melting inert gas shielded welding and stir friction welding.

4. The composition design method of a 6XXX series high-strength aluminum alloy welding filler material according to claim 1, characterized in that: The fusion ratio in step 3 is calculated as follows: fusion ratio = cross-sectional area of ​​melted parent metal / (cross-sectional area of ​​melted parent metal + cross-sectional area of ​​filler metal in weld).

5. The composition design method of a 6XXX series high-strength aluminum alloy welding filler material according to claim 1, characterized in that: The volatility of the easily burnable element in step 3 is calculated as follows: volatility = (Mg or Zn content calculated based on the fusion ratio - Mg or Zn content of the actual weld) / Mg or Zn content of the actual weld, where the easily burnable element is Mg or Zn.

Citation Information

Patent Citations

  • Preparation method for 5-series aluminum alloy welding wire containing rare-earth elements Nd and Ce

    CN110227892A

  • Al-Mg-Mn-Zn-Zr welding wire alloy cast ingot for high-strength fusion welding and preparation method thereof

    CN116000498A